2020
DOI: 10.3390/ma13081952
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Basalt Fiber-Reinforced Bottom Ash Cement Paste Composites

Abstract: Extinction of natural resources builds up pressure on governments to invest in research to find more sustainable resources within the construction sector. Earlier studies on mortar and concrete show that bottom ash and basalt fiber are independently alternative binders in the concrete sector. This study aims to use bottom ash and basalt fiber blends as alternative novel-based composites in pure cement paste. The strength and durability properties of two different percentages of bottom ash (40% and 50%) and thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Fibres that are most commonly used to reinforce mortars are made of steel, carbon, glass, polypropylene and basalt [ 41 , 42 , 43 , 44 ], although the use of other natural fibres, such as sisal, has also been reported [ 45 ]. As the basalt fibres used in this study are a relatively new material [ 46 , 47 , 48 , 49 , 50 ], the properties of composite materials (including cementitious mortars) with their addition have not been fully discovered yet, and intensive research is still recommended [ 42 ]. A summary of the studies carried out thus far on various types of mortars with the addition of basalt fibres was presented in [ 51 ], where the authors suggested the following.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibres that are most commonly used to reinforce mortars are made of steel, carbon, glass, polypropylene and basalt [ 41 , 42 , 43 , 44 ], although the use of other natural fibres, such as sisal, has also been reported [ 45 ]. As the basalt fibres used in this study are a relatively new material [ 46 , 47 , 48 , 49 , 50 ], the properties of composite materials (including cementitious mortars) with their addition have not been fully discovered yet, and intensive research is still recommended [ 42 ]. A summary of the studies carried out thus far on various types of mortars with the addition of basalt fibres was presented in [ 51 ], where the authors suggested the following.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they indicate no chemical reaction when in contact with some chemicals. Multiple potential applications of basalt fibre-reinforced cementitious materials are currently a subject of discussion in terms of sustainable development [ 7 , 50 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qin et al found similar results in their study and stated that as the rate of basalt ber increases, the tensile splitting strength increases (Qin et al 2018). In the study of Hana et al, the use of basalt ber up to 0.75% generally increased the exural strength, while the use of 1.5% basalt ber decreased the exural strength (Hana et al 2020). These different behaviors in exural strength may be due to the tendency of the bers to coagulation.…”
Section: Compressive and Flexural Strength Of Cement Based Compositesmentioning
confidence: 93%
“…Similar results were observed with mixtures made with glass ber (Tassew and Lubell 2014; Hong and Lubell 2015). Hana et al observed that unit weight values did not change much with the increase in ber ratio in cement pastes that they obtained by using different proportions of basalt ber (Hana et al 2020). In the study conducted by Borhan, as the basalt ber content increased, the unit weight values of the concrete decreased (Borhan 2012).…”
Section: Fresh State Properties and Unit Weights Of Cement Based Compositesmentioning
confidence: 97%
“…Rapid increment in construction works and urbanization brought greater demand for construction materials that have to do with the idea of sustainability, environmentally friendly, and low processing costs (Ash & Paste, 2020). Selection of building materials for construction is influenced by factors like climate, aesthetic, cost-effectiveness, availability, desired strength, hardness, etc.…”
Section: Introductionmentioning
confidence: 99%